PENEGAKAN HUKUM TERHADAP DELIK TERTINGGAL DALAM PEMERIKSAAN PERKARA YANG DILAKUKAN SECARA TERPISAH. - Isman, Muhammad Ismunanda; Candra, Mardi; Basuki, Basuki (LPPM Institut Pendidikan Nusantara Global, 2024)
It is not uncommon for the perpetrator of a crime to commit several crimes, meaning that the perpetrator of the crime commits a crime more than once, the crime itself must be tried by law, and it is the responsibility of law enforcement officials, usually to account for the actions of the perpetrator of the crime itself, the investigator conducts split case handling, meaning that crimes that have not been tried in the handling of the case are handled separately, this also results in different court decisions. In its application, it often contradicts Article 12 paragraph (4) of the Criminal Code which regulates the maximum imprisonment for a certain period of time and Article 71 of the Criminal Code which regulates the calculation of the offense left behind, so that in its application it contradicts the theory of legal objectives and law enforcement. As happened in the Robert Tantular case. The method in this research uses normative juridical, because the approach taken is based on the main legal material by examining theories, concepts, legal principles and laws and regulations and can also describe, situations, phenomena, or problems that refer to legal norms contained in various laws and regulations, court decisions. The author also uses case studies as a research strategy to investigate carefully about a program, event, activity, process, or group of individuals. The data used in this research includes primary data and secondary data. In practice in Indonesia, there are still mistakes in the application of law made by law enforcers, especially by the Panel of Judges, even though the provisions of underdeveloped offenses have also been regulated in the Criminal Code to limit the arbitrariness of law enforcement officials in enforcing the law related to underdeveloped offenses. Thus, in order to avoid mistakes in its application, technical guidance is needed related to the handling of underdeveloped criminal offenses by law enforcement officials so that law enforcement can run in accordance with the provisions of the legislation